Effects of logging residues and skid roads on litter decomposition rate and nutrient release of black pine (Pinus nigra Arnold) and scots pine (Pinus sylvestris L.) - Enez, Korhan; Savaci, Gamze; Sariyildiz, Temel (Hrvatsko Sumarsko Drustvo, 2022)
Needle litter decomposition rate and nutrient releases of pure stands of black pine and Scots pine under the three different micro-ecologic sites (skidding road, the logging residues and mineral topsoil) and the control site (non-harvesting site) were studied. The needle litters of Black pine and Scots pine were initially analysed for total carbon and nutrient concentrations (N, P, K, Ca, S, Mg, Mn, and Fe). The litter decomposition experiment using the litterbags method was carried out in the field for 18 months. The Scots pine needle litters decayed faster than the black pine litters. Both the Scots pine and Black pine needle litters showed higher mean mass losses under the mineral topsoil and the logging residues than under the skid road and the control site.
Keywords: nutrient; litter decomposition; hranjive tvari; Black and Scots pine; mikroekološko područje; vrste drveća; litter quality; micro-ecological areas; kvaliteta listinca; raspadanje listinca; 2. Zero hunger; 15. Life on land; 6. Clean water; 12. Responsible consumption; 11. Sustainability